'It was just you and your child': Single migrant mothers, generational storytelling and Australia's migrant heritage. (August 2020) - Dellios, Alexandra
On the 10 and 11 February 2016, former residents of one of Australia's post-war 'holding' centres for migrant arrivals presented evidence at a hearing for the site's inclusion on the Victorian Heritage Register. They were aware that the Victorian Heritage Register held few places of significance to post-war migrant communities, let alone working migrant women, which Benalla largely accommodated. They chose to retell their mothers' stories and explicitly expressed a desire to honour their mothers' memory at this hearing. This article will explore the impetus expressed by these former child migrants of Benalla to tell their mothers' stories and unpack its associated implications for the history and collective remembrance of Australia's post-war migrants. These former child migrants found a platform in the heritage hearing, a platform from which they could piece together their mothers' history and insist that it is a history worthy of heritage listing and public acknowledgement. On a broad level, I ask, what can a contentious history like Benalla's offer the history of post-war migration in Australia? Specifically, what role do generational stories of single working migrant women have in the remembering of migrant history and heritage practice in Australia?